The historical significance of African liberation – the views of South African History Education students - Wassermann, Johan M (Revista Electrónica Interuniversitaria de Formación del Profesorado, 2017)
Abstract This study drew on the views of South African first-year history education students who are studying to become teachers. In an open-ended survey they were asked to, by means of intellectual imagination, to express their views on what topics they would like to see as part of the school history curriculum. The purpose of this was to determine what they regarded as historically significant enough to study in history at school. The responses were analysed by means of open coding and read through Counsell’s conceptualisation of historical significance. What emerged was that the struggle against apartheid was viewed by only handful as an actual struggle for liberation against internal colonialism. The African liberation struggles against European colonialism fared even worse and was only imagined by a small number of students as worthy of inclusion in an imagined school history curriculum. At the same time at no stage were the struggled against apartheid linked to the broader African liberation struggle. What this speaks of is no only a South African exceptionalism but a view that the African liberation struggle are not really historically significant enough to be include in a imagined history curriculum.